The Crumbling Two-Story Architecture of Richard Powers’ Fictions - Thomas B. Byers (Transatlantica)
A prominent characteristic of Richard Powers’ technique is that his novels generally proceed by the alternating narration of two different stories. The relations of one story to another vary quite widely, however. On the diegetic level, the two may have a common protagonist, as in Galatea 2.2; or they may concern the different but circumstantially intersecting lives of disparate figures, as in The Echo Maker; or they may explore a possible chain of cause and effect, as in Gain. Most radically, in Plowing the Dark, their relation seems to be more or less purely metaphoric, with little or no metonymic connection at all. On the level of meaning, the two stories may seem to form unities by operating in conjunction or parallel or in a more oppositional or dialectical relation. This paper outlines the different permutations of the two-story structure in a range of Powers’ books. It also explores what, if anything, may be seen as the left-over, that which remains unassimilated to artistic or thematic unity, in various novels – and, if that remainder can be identified, what it might signify.